Eosinophil-rich tissue infiltrates in chronic myelomonocytic leukemia patients. Issue 12 (2nd December 2017) - Droin, Nathalie; Lucas, Nolwenn; Parinet, Vincent; Selimoglu-Buet, Dorothée; Humbert, Marc; Saada, Véronique; Lambotte, Olivier; Solary, Eric; Noël, Nicolas
Abstract: Chronic myelomonocytic leukemia (CMML) is a clonal hematopoietic disorder that associates dysplastic and proliferative features. Tissue inflammatory disorders occur in a fraction of CMML patients during the course of their disease. Here, we describe the occurrence of eosinophil-rich tissue inflammation, including eosinophilic pneumonia, chondritis, and cystitis, in CMML patients. Whole exome sequencing of leukemic cells did not identify a recurrent genetic abnormality among these three patients who were clinically improved by local or oral corticosteroids. Hypomethylating drugs were subsequently added in two of them, allowing decreasing corticosteroid doses and further treating their hematopoietic malignancy.